PROFIL KIMIA TUMBUHAN PERSEA AMERICANA MILL. INDONESIA - Asriani Ilyas (Teknosains, 2015)
Isolation and identification of secondary metabolites from extract of Persea Americana Mill. Plant had been performed. Separation techniques used consisted of extraction, fractionation, purification, and bioassay used Brin shrimp Lethality Test. The compounds obtained were tested and elucidated based on IR spectroscopy data. The compounds obtained were flavonoid (1) with LC50 = 24,342 μg/mL and alkaloid (2) with LC50 = 39,8 μg/mL.